A Dominant Mutation in the Stereocilia‐Expressing Gene TBC1D24 is a Probable Cause for Nonsyndromic Hearing Impairment. Issue 7 (6th May 2014) - Zhang, Luping; Hu, Lingxiang; Chai, Yongchuan; Pang, Xiuhong; Yang, Tao; Wu, Hao
<x xml:space="preserve">Abstract</x> By linkage analysis and whole exome sequencing, we identified a p.Ser178Leu heterozygous mutation of TBC1D24 as a probable cause for the late‐onset, progressive, non‐syndromic hearing impairment in a dominant deaf family. In perinatal mouse cochlea, we detected a restricted expression of Tbc1d24 in the stereocilia of the hair cells as well as in the spiral ganglion neurons. Our findings may shed new light on the specific function of TBC1D24 in the inner ear. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>